2021
DOI: 10.3390/jcm10194578
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Disease and Vitamin D Deficiency in Pregnant Women: Which Correlation with Preterm and Low-Weight Birth?

Abstract: Periodontal disease seems to be correlated with low vitamin D serum levels, preterm birth (PTB) and low birth weight (LBW), although the literature still lacks a consensus. This study aimed to investigate this correlation in a cohort of pregnant women over 20 weeks of gestation from the University Hospital “Maggiore della Carità”, Novara, Italy. We assessed serum levels of vitamin D and oral health status through the following indexes: Oral Hygiene Index (OHI), Plaque Control Record (PCR), Gingival Bleeding In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 95 publications
(95 reference statements)
1
24
0
Order By: Relevance
“…The constant deposit of bacterial biofilm on the teeth triggers a chronic inflammatory condition ranging from a reversible low-level (gingivitis) to irreversible higher level of inflammation (periodontitis) and tooth mobility/loss [ 126 ]. In this context, microbial products and inflammatory mediators might enter the systemic circulation and reach distant organs, supporting the genesis of systemic pathologies [ 127 , 128 , 129 , 130 ]. Nutrition is a critical determinant of immune responses [ 131 ] because nutrients derived from food sources show a strong interaction with the immune system cells [ 132 ] and nutritional deficiency might impair the immune response and predispose the individual to infection [ 133 , 134 ].…”
Section: Oral Frailty: a Detrimental Issuementioning
confidence: 99%
See 1 more Smart Citation
“…The constant deposit of bacterial biofilm on the teeth triggers a chronic inflammatory condition ranging from a reversible low-level (gingivitis) to irreversible higher level of inflammation (periodontitis) and tooth mobility/loss [ 126 ]. In this context, microbial products and inflammatory mediators might enter the systemic circulation and reach distant organs, supporting the genesis of systemic pathologies [ 127 , 128 , 129 , 130 ]. Nutrition is a critical determinant of immune responses [ 131 ] because nutrients derived from food sources show a strong interaction with the immune system cells [ 132 ] and nutritional deficiency might impair the immune response and predispose the individual to infection [ 133 , 134 ].…”
Section: Oral Frailty: a Detrimental Issuementioning
confidence: 99%
“…Moreover, in geriatric subjects with serious illnesses and functional dependency, oral health problems are often underdiagnosed and untreated [ 239 , 240 ]. Increasing evidence also reveals significant interactions between oral health and general health that are unidirectional and often bidirectional [ 127 , 129 , 130 , 241 , 242 ]. It has been hypothesized that a strict correlation between oral health and quality of life, as reported by Hoeksema et al [ 3 ] while assessing the oral health in community-living elderly, demonstrated that general health and HRQoL were higher in older people with remaining teeth and implant-supported dentures than the edentulous ones.…”
Section: Oral Health Management For Older Subjectsmentioning
confidence: 99%
“…Moreover, the importance of thorough antenatal care was confirmed in the article by Ferrillo et al [2], who reported a high prevalence of preterm birth among women with poor oral health and vitamin D deficiency. Their results underline the need to constantly expand the knowledge on various causal factors.…”
mentioning
confidence: 92%
“…[ 4 ]. In this context, particularly in women, vitamin D deficiency showed to be related to an increased risk of fractures and falls [ 5 , 6 , 7 ]; osteoarthritis [ 8 ]; sarcopenia [ 9 , 10 ]; cardiovascular diseases [ 11 ]; malignancy [ 12 , 13 ]; neurological diseases [ 14 , 15 , 16 ]; COVID-19 [ 17 ]; poor oral health [ 18 , 19 ]; periodontal diseases, especially during pregnancy [ 20 ]; and temporomandibular disorders (TMD) [ 21 ].…”
mentioning
confidence: 99%
“…However, we are aware that there is a high heterogeneity among oral health outcomes, considering the different parameters that might be investigated. Moreover, the correlation between serum levels of 25(OH)D3 and periodontitis has been widely investigated, with contrasting results, albeit most studies confirmed this hypothesis [ 33 , 34 , 35 ], particularly in pregnant women [ 18 ] or in those affected by breast cancer [ 20 ]. However, to date, although the study quality of the scientific literature has proven to have some limitations, vitamin D supplementation seemed to improve oral health status [ 19 ].…”
mentioning
confidence: 99%